3(5n+5)-6=2(3n-6)

Simple and best practice solution for 3(5n+5)-6=2(3n-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5n+5)-6=2(3n-6) equation:


Simplifying
3(5n + 5) + -6 = 2(3n + -6)

Reorder the terms:
3(5 + 5n) + -6 = 2(3n + -6)
(5 * 3 + 5n * 3) + -6 = 2(3n + -6)
(15 + 15n) + -6 = 2(3n + -6)

Reorder the terms:
15 + -6 + 15n = 2(3n + -6)

Combine like terms: 15 + -6 = 9
9 + 15n = 2(3n + -6)

Reorder the terms:
9 + 15n = 2(-6 + 3n)
9 + 15n = (-6 * 2 + 3n * 2)
9 + 15n = (-12 + 6n)

Solving
9 + 15n = -12 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
9 + 15n + -6n = -12 + 6n + -6n

Combine like terms: 15n + -6n = 9n
9 + 9n = -12 + 6n + -6n

Combine like terms: 6n + -6n = 0
9 + 9n = -12 + 0
9 + 9n = -12

Add '-9' to each side of the equation.
9 + -9 + 9n = -12 + -9

Combine like terms: 9 + -9 = 0
0 + 9n = -12 + -9
9n = -12 + -9

Combine like terms: -12 + -9 = -21
9n = -21

Divide each side by '9'.
n = -2.333333333

Simplifying
n = -2.333333333

See similar equations:

| 2y^2-2y=0 | | i=z^8 | | 9(v+7)=-3v+27 | | 10=3+c | | (z^8)-i=0 | | 9x+6-12x=-7+2x-12+5x | | 2r(r+3)=0 | | 7(w-4)+8w=2 | | 3x+3y-3x+4y= | | 2/5x-1/3=2/15 | | 4a^3-44a^2=0 | | -6u+3(u+4)=-18 | | 8y=7y+1 | | x^2+x+6=4x+4 | | 4r^2+28r=0 | | 2/3•3=6/3 | | 2/3-1/6x=5/12 | | 11b+7=4 | | 4/3=n-4/n | | 49=6x+x | | 3n-3=-8(5+5n) | | 5-3a=2 | | 45=4x^2+x^2 | | 50=x+22 | | 3n-9n=0 | | 3z/8-7=-5 | | 10(2x+3)=50 | | 0.4y+5.6=2.4 | | 5n-21=-111 | | x+2=2x+50 | | 14-6n=-8(-7n+6) | | (8/7)=(3x/86) |

Equations solver categories